The Effect Of Social Simulation Learning Model On Students' Social Attitudes, Morality, And Courtesy - Hafizah Hafizah; Yolla Ramadani (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to determine the effect of the social simulation learning model on the social attitudes, morality, and courtesy of students in higher education. The research involved 52 students selected randomly from second-semester students at two universities during the odd semester of 2022/2023. Data on learning independence were collected using a questionnaire. This study employed a quasi-experimental research design. Prerequisite tests were conducted using normality and homogeneity tests. Normality was tested using the Kolmogorov-Smirnov test, while homogeneity was tested with homogeneity variance. If the prerequisites were met, a homogeneity test was performed. The research findings indicate that the prerequisite tests were fulfilled, confirming that the data were normally distributed and homogeneous. The homogeneity test results concluded that there is a significant effect of the social simulation model on social attitudes, morality, and courtesy. The social simulation model positively influences these aspects, with significant differences observed between the two groups after the treatment was administered. The normality and homogeneity tests ensured that the data met the criteria for valid statistical analysis. These findings highlight the importance of using experience-based learning methods to develop students' interpersonal skills, which will positively impact their academic life.